2021
DOI: 10.1017/s0031182021000548
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus cyst fluid suppresses inflammatory responses by inhibiting TRAF6 signalling in macrophages

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Neutrophils exhibit anti-parasitic effects through phagocytosis, degranulation, and the formation of neutrophil extracellular trapping networks (NETs) ( Díaz-Godínez and Carrero, 2019 ; Omar and Abdelal, 2023 ). Similarly, macrophages may hinder parasite survival through phagocytosis, NO production, and pro-inflammatory cytokine release ( Silva-Álvarez et al, 2016 ; Lin et al, 2021 ). Therefore, the downregulation of chemokine expression in MSCs induced by parasite antigens may facilitate the innate immune evasion of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils exhibit anti-parasitic effects through phagocytosis, degranulation, and the formation of neutrophil extracellular trapping networks (NETs) ( Díaz-Godínez and Carrero, 2019 ; Omar and Abdelal, 2023 ). Similarly, macrophages may hinder parasite survival through phagocytosis, NO production, and pro-inflammatory cytokine release ( Silva-Álvarez et al, 2016 ; Lin et al, 2021 ). Therefore, the downregulation of chemokine expression in MSCs induced by parasite antigens may facilitate the innate immune evasion of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cytokine levels of IL‐10 were significantly increased in the cell culture supernatant after 24 h. From the traditional point of view, excretory/secretory proteins (ESP) of helminths can shift immune responses from Th1 toward Th2 64–66 . Recently, Lin et al 67 showed that HCF attenuates inflammatory responses in macrophage cell lines (both mice [peritoneal macrophages and RAW 264.7 cells] and human [THP‐1] macrophages), which supports our findings. In a study by Pan et al, 68 the effects of ESPs derived from E. granulosus protoscoleces on the differentiation of CD19 + B cells, which were isolated from the spleen of normal or infected C57BL/6 or TLR‐2−/− mice, were investigated and suggested that these ESPs can modulate immune responses via stimulating B cells to generate B10 cells with higher levels of IL‐10.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that innate immune pathways such as inflammatory vesicles and Toll-like receptor activation, and hepatocyte apoptosis are the host’s primary line of defense against the progression of liver Echinococcosis infection ( Vuitton, 2003 ; Inclan-Rico and Siracusa, 2018 ; Bakhtiar et al., 2020 ). Recently, more and more studies have found that growth metabolic pathways are activated during the process of liver Echinococcosis infection and interact with the immune-inflammation and fibrosis pathways to jointly regulate the outcome of the disease ( Seoane et al., 2016 ; Cheng et al., 2017 ; Liu et al., 2017 ; Yin et al., 2018 ; Wang et al., 2019 ; Lin et al., 2021 ; Yang et al., 2022 ). However, to date, few studies have addressed the various outcomes following interventions in growth metabolic pathways during the progression of liver Echinococcosis .…”
Section: Ghrelin and Liver Echinococcosismentioning
confidence: 99%
“…In addition, clinical studies have also pointed out that effective anti-infective treatment of Echinococcosis is positively correlated with maintaining a high response of Th1 type cellular immunity, while ineffective anti-infective treatment is more closely related to maintaining a high response of Th2 type cellular immunity ( Siracusano et al., 2012 ; Gottstein et al., 2017 ). In addition, studies have shown that the NF- κB inflammatory signaling pathway ( Tilioua et al., 2020 ; Lin et al., 2021 ) and the TGF-β1/Smad3 fibrosis signaling pathway ( Wu et al., 2004 ; Banas et al., 2007 ; Liu et al., 2016 ; Tian et al., 2020 ) play a key role in regulating the immune-inflammation and fibrosis state of the host infected by Echinococcosis . Inhibition of these pathways could attenuate the host’s protective immune response and promote the disease progression of liver Echinococcosis infection.…”
Section: Ghrelin and Liver Echinococcosismentioning
confidence: 99%
See 1 more Smart Citation